2022
DOI: 10.1155/2022/1034535
|View full text |Cite|
|
Sign up to set email alerts
|

Eye Sign is an Alternative for Evaluation of the Microcirculation in Patients with Systemic Sclerosis

Abstract: Objectives. To investigate consistency between eye sign and nailfold video capillaroscopy (NVC) in systemic sclerosis (SSc) patients and to evaluate eye sign with various parameters of disease and potential pulmonary involvement. Methods. A total of 60 SSc patients and 20 healthy individuals were enrolled. 20 SSc patients were complicated with pulmonary arterial hypertension (PAH); 20 SSc patients with interstitial lung diseases (ILD); 20 SSc patients without pulmonary involvement. All subjects were assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Copared to conjunctival microcirlation examination, the detection of the eye signs is more simple, as they can be observed using a conventional slit lamp or even with the naked eye. Clinical validation of eye signs demonstrates their high accuracy in assessing thrombosis or hypercoagulability, exhibiting a strong correspondence with nailfold capillary microcirculation [25].…”
Section: Discussionmentioning
confidence: 99%
“…Copared to conjunctival microcirlation examination, the detection of the eye signs is more simple, as they can be observed using a conventional slit lamp or even with the naked eye. Clinical validation of eye signs demonstrates their high accuracy in assessing thrombosis or hypercoagulability, exhibiting a strong correspondence with nailfold capillary microcirculation [25].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%